RETINOBLASTOMA: TOPICAL ISSUES AND THEIR SOLUTIONS - Arman Khozhayev; Dinash Alipkaliyeva; Madina Karshygabek; Dinara Abimolda (European Research Materials, 2026)
this scientific and analytical work presents modern clinical and diagnostic data concerning the most common malignant intraocular tumor in children – retinoblastoma. The issues of etiopathogenesis, genetic and molecular features of this pathology, assessment of the role of biomarkers in diagnostics and prognosis of the disease are covered in detail. Promising directions for the development of new and improved diagnostic and therapeutic approaches, genetic causes of this pathology, possibilities of whole genome sequencing for studying the mutation landscape, currently used classification systems of retinoblastoma, available possibilities of clinical screening are described. The publication shows that studies of the molecular basis of the disease also led to deciphering subsequent events and, thus, to the discovery of biomarkers and associated targeted therapies. In addition, improvements in molecular biology methods contributed to the development of effective methods of early diagnostics, genetic counseling and disease prevention. The issues of visual acuity assessment and improving the quality of life of patients are also comprehensively considered